POLITENESS STRATEGY ANALYSIS ON THE TONIGHT SHOW STARRING JIMMY FALLON - Adela Yusniati; Marwito Wihadi; Wulan Rahmatunisa (UIBU, 2023)
The purpose of this study is to identify the politeness strategies used by Taylor Swift and Paul Rudd in the Tonight Show with Jimmy Fallon YouTube videos